2008
DOI: 10.1007/s11259-008-9046-x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of paramphistomosis of sheep (Ovis aries L.) in the north west temperate Himalayan region of India

Abstract: An epidemiological study with the objective to assess the prevalence of paramphistomosis in association with season, age, sex and breed was carried out in naturally infected sheep over a period of two years from February 2005 to January 2007. Gastrointestinal tract (GIT) and faecal examination were conducted monthly to monitor the seasonal occurrence of paramphistomosis. 793 sheep were examined in the first year, out of which 7.06% were positive for Paramphistomum infection. In the second year, 740 animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 6 publications
7
19
2
Order By: Relevance
“…Most infections of adult fluke are harmless although large number of flukes can cause a chronic ulcerative rumenitis with ruminal papillae atrophy (Love and Hutchinson 2003).The immature forms of P. cervi caused more severe damage in the duodenal tissue, whereas the mature form inflicted mild tissue damage in the rumen of the experimental kids. In present study, prevalence of Paramphistomosis in sheep was at 0.2 % average yearly, somehow throughout a year was between 0 and 2.4 %, which is much lesser than that recorded in Heilongjiang Province in People's Republic of China (Wang et al 2006), in Maiduguri in Nigeria (Biu and Oluwafunimilayo 2004), is similar to Himalayan region of India (Tariq et al 2008) and to that found in the Fars province of Iran (Moghaddar and Khanitapeh 2003). The highest prevalence of Paramphistomum spp.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Most infections of adult fluke are harmless although large number of flukes can cause a chronic ulcerative rumenitis with ruminal papillae atrophy (Love and Hutchinson 2003).The immature forms of P. cervi caused more severe damage in the duodenal tissue, whereas the mature form inflicted mild tissue damage in the rumen of the experimental kids. In present study, prevalence of Paramphistomosis in sheep was at 0.2 % average yearly, somehow throughout a year was between 0 and 2.4 %, which is much lesser than that recorded in Heilongjiang Province in People's Republic of China (Wang et al 2006), in Maiduguri in Nigeria (Biu and Oluwafunimilayo 2004), is similar to Himalayan region of India (Tariq et al 2008) and to that found in the Fars province of Iran (Moghaddar and Khanitapeh 2003). The highest prevalence of Paramphistomum spp.…”
Section: Discussionsupporting
confidence: 53%
“…Rangel-Ruiz et al (2003) from Tabasco, Mexico reported that the sheep primarily were affected throughout the rainy and windy seasons, during summer, autumn and in the beginning of the winter (Rangel-Ruiz et al 2003). Tariq et al (2008) reported that highest ovis infection was in summer and the lowest in winter. In the North West temperate of Himalayan area of India a similar study demonstrated the severity and intensity of infection, reaching to its maximum in late summer and autumn season in drier months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subtropical and tropical areas, the infection leads to economic losses related to mortality and low productivity (Spence et al 1996;Kilani et al 2003). Paramphistomosis, caused by a group of amphistome species, in cattle has a wide range of geographic distribution and is prevalent in several states of India including Punjab (Chhabra et al 1972;Hassan et al 2005) and Kashmir valley (Tariq et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In India, 20 species were described and classified by Dutt (1980) in ruminants but the predominant species are Paramphistomum epiclitum, Gigantocotyle explanatum, Gastrothylax crumenifer, Cotylophoron cotylophorum and Fischoederius elongatus, with prevalence rate of 3-70% in different states (Hassan et al, 2005;Tariq et al, 2008;Swarnakar et al, 2014).The adult stages generally have low pathogenicity while the pathological changes induced by the immature stage in the gastro-intestinal (GI) tract of the ruminant are responsible for severe economic losses (Singla et al, 1998;Silvestre et al, 2000).…”
Section: Introductionmentioning
confidence: 99%